Do Organizational Commitment and Work Stress Moderated by Locus of Control Influence Auditor Performance? Evidence from Banking Institution - Herisma, Jhon; Diantimala, Yossi; Saputra, Mulia (Universitas Syiah Kuala, 2022)
AbstractObjective This study aims to determine the effect of organizational commitment and work stress on auditor performance with locus control as a moderating variable in a banking institution.Design/methodology The population and sample in this study were all internal auditors spread across all branch offices at Bank Sejahtera, totaling 33 people. Sources of data using primary data derived from distributing questionnaires to research respondents.Results The results showed that the variables of organizational commitment, job stress, and locus of control simultaneously affect the performance of internal auditors. Then, organizational commitment has a positive effect on the performance of internal auditors. Furthermore, work stress has a negative effect on auditor performance. Locus of control has a positive effect on the performance of internal auditors. Next, locus of control strengthens the relationship between organizational commitment and internal auditor performance. Likewise, locus of control also strengthens the relationship between job stress and the performance of internal auditors.Research limitations/implications This study is only conducted at one state-owned bank in Banda Aceh. Implementation at different banks with different management styles may show different results.Novelty/Originality This research provides an empirical analysis about locus of controls role in strengthening the relationship between organizational commitment and internal auditor performance as well as the relationship between job stress and the internal auditor performance.